Computational analysis and experimental calibration of cold isostatic compaction of Mg-SiC nanocomposite powders. (June 2021) - Rahimi Mehr, F.; Salavati, M.; Morgenthal, A.; Kamrani, S.; Fleck, C.
Graphical abstract: Highlights: Finite Element Modeling is performed to characterize the compaction behavior of Mg-SiC using the modified Drucker-Prager-Cap (DPC) model. Increasing SiC nanoparticles from 1% to 10 vol% led to harder compressibility, increased maximum equivalent pressure stress value 717.2 MPa to 737.1 MPa, decreased relative density value 94.63% to 88.67%, and enhanced inhomogeneous density distribution. Computational modeling results converged well to the experimental results indicating the effectiveness of the CIP modeling using a modified DPC model. Abstract: The consolidation process and density distribution of Mg-SiC nanocomposite powder were studied using computational finite element modeling (FEM) and experimental approaches. Cold isostatic pressing (CIP) was employed for producing fully dense Mg-SiC nanocomposites with a homogeneous distribution of SiC nanoparticles. The elastoplastic modified Drucker-Prager Cap (DPC) model was applied to predict SiC nanoparticle density distribution effects on the milled powder compressibility after the CIP. The FEM results revealed that increasing SiC nanoparticles from 1% (M1Sn) to 10% (M10Sn) volume leads to harder compressibility, increasing the maximum equivalent pressure stress value 717.2 to 737.1 MPa, and decreasing the relative density value 94.63% to 88.67%. The maximum element volume (EVOL) for pure Mg (MM), M1Sn, and M10Sn powders was estimated as 21.69, 20.13, and 15, respectively. The model is validated by comparing finite element simulations with experimental results of relatve density and reduction of volume under 700 MPa cold isostatic pressure for MM, M1Sn, and M10Sn powders. The finite element modeling results of samples after the CIP process were consistent with the experimental results. These results indicate the effectiveness of the modified DPC model and confirmed compaction behavior and relative density of Mg-SiC nanocomposite powders.